Multi-objective optimization of an auto panel drawing die face design by mesh morphing - Liu, Wei; Yang, Yuying (Computer aided design, 2007)
In order to facilitate the tryout or simulation process at the end of a manual auto panel drawing die face design process, we use finite element analysis (FEA) and a multi-objective genetic algorithm (MOGA) to find all the Pareto optimal solutions in one go and to achieve the optimal design of an auto panel drawing die face instead of transforming multi-objective functions into a single objective function, and employ a novel mesh morphing technique to achieve fast modification of parametric or non-parametric addendum surfaces and binder surfaces on drawing die faces without going back to CAD for reconstruction of geometric models or to FEA for remodeling. We use an auto panel drawing die face design process as an example to illustrate the application and effectiveness of this proposed approach, and come to the conclusion that the proposed approach is more effective than the traditional manual FEA method and the ‘trial-and-error’ approach in optimizing an auto panel drawing die face design.